A Study of Growth Mechanism of KDP and ADP Crystals by Means of Quantum Chemistry - Asakuma, Y; Li, Qin; Ang, Ming; Tade, Moses; Maeda, K.; Fukui, K. (Elsevier BV North-Holland, 2008)
Impurity adsorption, crystal growth by adsorption of growth unit and step-pinning mechanism of metal ion adsorption were investigated for potassium dihydrogen phosphate (KDP; KH2PO4) and ammonium dihydrogen phosphate (ADP; NH4H2PO4) by quantum chemistry. In this study, the ideal crystal morphologies, the growth unit and the crystal surface with and without metal ions were calculated and analyzed by using electrostatic property. It is found that the computational results based on electrostatic potential distribution can account for the observed behaviours on KDP and ADP crystal growth. PACS: 81.10.Dn